Global school-based student health survey: country profiles and survey results in the eastern Mediterranean region countries - Elham Abdalmaleki; Zhaleh Abdi; Sahand Riazi Isfahani; Sara Safarpoor; Bahar Haghdoost; Saharnaz Sazgarnejad; Elham Ahmadnezhad (BMC, 2022)
Abstract Background The increasing prevalence of non-communicable diseases (NCDs) has some major implications on many countries to achieve universal health coverage. This study aimed to investigate the implementation of Global School-based Student Health Survey (GSHS), which is used to assess the risk factors of NCDs among children and adolescents in the eastern Mediterranean region (EMR). Methods This study was a meta-analysis and systematic literature review of 2001-2018 published studies, which were found by searching PubMed, Google Scholar, WHO, and CDC databases. In this study, the target group was students aged between 13 and 17 years old. GSHS implementation as well as risk factors of NCDs were compared across different countries. The random-effect model for meta-analysis was considered at 95% confidence interval. Result In the EMR, 19 countries have implemented GSHS at least once following the survey manual (37 surveys). Overall, 201,795 students were included in our analysis. The overall estimation prevalence rateof the overweight was 24.5% (20.6-28.8), obesity was 7.3% (5.4-9.5), insufficient physical activity was 82.4% (80.7-84.1), tobacco usage was 14.3% (10.53-18.67), and smoking was 9.6% (8.1-11.3), respectively. Among those aged 13 to 17 years old, these rates were estimated as 19.8 (13.2-27.3), 9.7 (6.2-14.0), 86.1 (84.1-87.9), 17.8 (11.8-24.7), and 11.5 (9.4-13.8), respectively. Conclusion GSHS has been widely implemented across EMR countries. Using nationally representative data, the results show that more efforts are needed to target the NCDs risk factors among adolescents in the region.